THE ANALYSIS OF EMOTIONAL ABUSE BASED ON RAPUNZEL’S EXPERIENCES IN DISNEY ANIMATED FILM TANGLED - Azizah, Septia Nur; Wulandari, Diyah Fitri (Jurnal Ilmiah Sultan Agung, 2024)
This is a study on emotional abuse analysis based on Rapunzel's experience in the Disney animated film Tangled. The objectives of this study are to identify the categories of emotional abuse experienced by Rapunzel in the Disney animated film Tangled, and to explain the effect of emotional abuse experienced by Rapunzel in the Disney animated film Tangled. This study used a qualitative descriptive method to analyze the categories and effects in the Disney animated film Tangled. The data is taken from the film script such as dialog, narration, and monologue. The steps used to collect data such as watching movies, reading movie scripts, identifying data, clarifying data, and reducing data. This study, the found four categories of emotional abuse. Rejecting, terrorizing, isolating, and exploiting. There were five data about rejecting, two data about terrorizing, two data about isolating, and one data about exploiting. Then the writer also found the effects of emotional abuse based on the four categories above. Rejecting makes the victim feel worthless, terrorizing makes the victim feel scared and intimidated, isolating makes it difficult for the victim to interact with others, exploiting uses the victim for the perpetrator's benefit.Keywords: Emotional abuse, Child rejection, Tangled